2010
DOI: 10.1111/j.1365-2427.2010.02412.x
|View full text |Cite
|
Sign up to set email alerts
|

Applying systematic conservation planning principles to palustrine and inland saline wetlands of New Zealand

Abstract: Previous attempts to identify nationally important wetlands for biodiversity in NewZealand were based on expert panel opinions because quantitative approaches were hampered by a lack of data. We apply principles of systematic conservation planning to remote sensing data within a geographical information system (GIS) to identify nationally important palustrine and inland saline wetlands. 2. A catchment-based classification was used to divide New Zealand into 29 biogeographic units. To meet representation goals,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
62
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(63 citation statements)
references
References 43 publications
(65 reference statements)
1
62
0
Order By: Relevance
“…MARXAN was used for systematic conservation planning Tulloch et al, 2014 Terrestrial Protect Three management zones for fox were planned: (1) no fox management, (2) low-intensity management (2 baiting events per year), (3) high-intensity management (4 baiting events per year)-−17% operational objectives for the distribution of the target species. Prioritization of sites was based on spatially explicit biodiversity values, feasibility and management costs, and estimates of cost effectiveness Ausseil et al, 2011 Transitional Avoid Identification of an optimal set of wetland sites by sequentially choosing wetlands that contribute most to a measure of condition and complementarity. Condition was used to give less importance to wetland sites with degraded ecological integrity.…”
Section: Approaches Applied To Address Biological Invasions In Consermentioning
confidence: 99%
See 2 more Smart Citations
“…MARXAN was used for systematic conservation planning Tulloch et al, 2014 Terrestrial Protect Three management zones for fox were planned: (1) no fox management, (2) low-intensity management (2 baiting events per year), (3) high-intensity management (4 baiting events per year)-−17% operational objectives for the distribution of the target species. Prioritization of sites was based on spatially explicit biodiversity values, feasibility and management costs, and estimates of cost effectiveness Ausseil et al, 2011 Transitional Avoid Identification of an optimal set of wetland sites by sequentially choosing wetlands that contribute most to a measure of condition and complementarity. Condition was used to give less importance to wetland sites with degraded ecological integrity.…”
Section: Approaches Applied To Address Biological Invasions In Consermentioning
confidence: 99%
“…Hence, invasive alien species were avoided through the selection of habitats that were in good condition, i.e., less affected by cumulative impacts. Ausseil et al (2011) developed a systematic conservation routine in R for the identification of an optimal set of wetland sites by sequentially choosing wetlands that contribute most to the preservation of national wetland biodiversity. The selection criteria were: (1) naturalness condition; (2) complementarity with already selected sites; and (3) irreplaceability.…”
Section: Approaches Applied To Address Biological Invasions In Consermentioning
confidence: 99%
See 1 more Smart Citation
“…Ausseil et al (2011) have improved the accuracy of wetland mapping and identified changes since pre-European time. These recent analyses, together with the LUM, permit a synthesis of information for assessing recent trends of natural habitat provision in New Zealand.…”
Section: Proposed Assessment Of Natural Habitat Provisionmentioning
confidence: 99%
“…The decline in many native freshwater fish is also attributed to the loss and degradation of wetlands (Sorrell & Gerbeaux, 2004). Ausseil et al (2011) estimated that the pre-human extent of wetlands was about 2.4 million ha, that is, about 10% of the New Zealand mainland. The latest extent (mapped in 2003) was estimated at 250,000 ha or 10% of the original coverage.…”
Section: Freshwater Wetlandsmentioning
confidence: 99%